Type 2 AGN host galaxies in the Chandra-COSMOS legacy survey: No evidence of AGN-driven quenching - Suh, H; Civano, F; Hasinger, G; Lusso, E; Lanzuisi, G; Marchesi, S; Trakhtenbrot, B; Allevato, V; Cappelluti, N; Capak, P; Elvis, M; Griffiths, R; et al. (IOP Publishing, 2017)
We investigate the star formation properties of a large sample of ∼2300 X-ray-selected Type 2 Active Galactic Nuclei (AGNs) host galaxies out to z ∼ 3 in the Chandra COSMOS Legacy Survey in order to understand the connection between the star formation and nuclear activity. Making use of the existing multi-wavelength photometric data available in the COSMOS field, we perform a multi-component modeling from far-infrared to near-ultraviolet using a nuclear dust torus model, a stellar population model and a starburst model of the spectral energy distributions (SEDs). Through detailed analyses of SEDs, we derive the stellar masses and the star formation rates (SFRs) of Type 2 AGN host galaxies. The stellar mass of our sample is in the range of 9 < log 1 M M stellar 2 with uncertainties of ∼0.19 dex. We find that Type 2 AGN host galaxies have, on average, similar SFRs compared to the normal star-forming galaxies with similar Mstellar and redshift ranges, suggesting no significant evidence for enhancement or quenching of star formation. This could be interpreted in a scenario, where the relative massive galaxies have already experienced substantial growth at higher redshift (z > 3), and grow slowly through secular fueling processes hosting moderate-luminosity AGNs.